2019
DOI: 10.3889/oamjms.2019.825
|View full text |Cite
|
Sign up to set email alerts
|

Live Birth Rates in Poor Responders’ Group after Previous Treatment with Autologous Platelet-Rich Plasma and Low Dose Ovarian Stimulation Compared with Poor Responders Used Only Low Dose Ovarian Stimulation Before in Vitro Fertilization

Abstract: BACKGROUND: This prospective pilot study determined the efficacy of previous transvaginal intraovarian injection with autologous platelet-rich plasma (PRP) in poor ovarian responders (PORs) fulfilling the Bologna criteria before in vitro fertilisation (IVF)/intracytoplasmic sperm injection (ICSI) with low dose ovarian stimulation. Current knowledge of efficient treatment for PORs is limited and often contradictory; also, LBRs of IVF remains disappointingly low. AIM: We assessed the live birth rates (LBRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…They reported that IP injection of PRP in POI rats increased the healthy primary and antral follicle counts, and they pointed out PRP as a protective agent against ovotoxic chemicals [31]. Along with the conduction of experiments involving intra-ovarian injection of PRP in animal models, some clinical trials have been started in human, opening hopes and therapeutic avenues in ovarian regeneration [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that IP injection of PRP in POI rats increased the healthy primary and antral follicle counts, and they pointed out PRP as a protective agent against ovotoxic chemicals [31]. Along with the conduction of experiments involving intra-ovarian injection of PRP in animal models, some clinical trials have been started in human, opening hopes and therapeutic avenues in ovarian regeneration [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Talking about suitable clinical settings to administrate PRP, transvaginal ultrasound-guided injection is a good candidate, since it is a nonsurgical technique that allows the clinicians to inject biological products like cells/PRP directly into the ovarian tissue. This technique is performed under sedation and is basically the same method used for an egg aspiration/retrieval during IVF/ICSI operation [32,51]. As described above, stem cell transplantation is another putative therapeutic option for POI patients and potentially more powerful in combination with PRP; however, stem cell therapy is sometimes associated with tumorigenesis, making this approach less safe than others [52].…”
Section: Discussionmentioning
confidence: 99%
“…In the last year a "glimpse of new hope" for POR-IVF patients has been suggested by two preliminary publications (112,113). In these reports, autologous platelet-rich plasma (PRP) was injected intraovarially by transvaginal sonographic guidance, before the IVF COH (112,113).…”
Section: Autologous Platelet-rich Plasmamentioning
confidence: 99%
“…In the last year a "glimpse of new hope" for POR-IVF patients has been suggested by two preliminary publications (112,113). In these reports, autologous platelet-rich plasma (PRP) was injected intraovarially by transvaginal sonographic guidance, before the IVF COH (112,113). The preliminary results suggest a trend toward better implantation rates and LBRs in those POR patients who have received the intraovarian PRP injections (112,113).…”
Section: Autologous Platelet-rich Plasmamentioning
confidence: 99%
See 1 more Smart Citation